PENGARUH UMUR DAN POSIS! DALAM POHON TERHADAP BEBERAPA SIFAT FISIS KAYU - Suparman Karnasudirdja; Edi Sarwono (Jurnal Penelitian Hasil Hutan, 1989)
Pinus  merkusii   or locally   known  as Tusam,   is one of the plantation  species  extensively   cultiuated  in the uarious part of  Indonesia.    The  uses  of  its  wood  uary  from  chopstick   and  ice cream  spoon  to some  construction   item  such  as trans- mission pole,  and a possible  use of  its wood  for cooling  tower is still being studied.The paper  describes  study   result  of  the  effect  of  tree  age  and  position   within   tree  on  some  physical  properties   (Specific grauity,   moisture  content,   uolumetric  shrinkage   and fiber saturation  point).   The  results  were computed  using  the nested  or hierarchical  classification  analysis,  and  the differences   between  means  tested  using  Tukey's  w procedure.The  results  shows  that  the tree  age effect  significantly   the green and air-dry  specific gravity,   The other properties do not  seem  to  be affected. Between  tree differences   affect  significantly    the air-dry  moisture  content  only.  Height  within  tree does  affect  uery  significantly   the  uolumetric   shrinkage  from  green  to ouen dry  condition;  and from  air-dry  to ouen  dry condition.   The ouerall  mean and standard deviation  ualues for each  property   had been calculated  and  the  result  presented.